Analysis of Grammatical Errors in a Written Essay of Final Year University Students - Thomas EKPE, Lucy (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
This study investigates grammatical errors in the written performance of the final year students of the Department of English and Literature, University of Benin, Benin City. One hundred (100) students were purposively selected for this study. Aspects of grammatical error investigated are classified into five grammatical categories which are: register adaptation, nominalization, lexico-grammars, sentence fragmentation and run-on sentence. Data for this study were collected through an essay writing which six topics where given to the students to pick anyone of their choice topic to write on. The theoretical frameworks adopted for the study are: Error Analysis (EA) and Content Analysis. The study attempted to examine the written production of the subjects studied and identify the specific writing difficulties observable in their written English. Data for the study were presented in tables, while the analyses were done by the use of frequency and simple percentages. The study found that the inability of the respondents to internalize the basic rules of the grammar of the English language, ignorance in the use of English expressions in particular field of discourse, faulty sentence structure, unawareness of the features of connected written discourse and direct transfer of usages from the first language (MT) to the second language were some of the major problems which negatively affected the respondents’ essays. This calls for intensive study of writing skills from first year students of the university so as to help the students develop their writing habits before getting to final year.